Pengaruh Perlambatan Ekonomi Nasional TerhadapPertumbuhan Ekonomi Provinsi Kalimantan Barat - Didi Rahmat (STIE 'INDONESIA' Pontianak, 2015)
This study investigates the effects of Indonesia Economic growth (IDR exchange rate, Inflation and Gross Domestic Brutto) on Regional economic growth of West Kalimantan (Gross Domestic Regional Brutto). This research use series range data from 2013 to the early 2015. Vector Auto regression (VAR) was used for data analysis. As a result that find Inflation rate and IDR exchange rate have a significant and positive impact to the Gross Domestic Regional Bruto Province of Kalimantan Barat. In other way, Gross Domestic Brutto has not an impact to Gross Domestic Regional Brutto Province of West Kalimantan